Application of Mind Mapping Learning Models to Improve Students’ Reading Skill in 4th Grade of Primary School - Indra Suhendra; Rahman Rahman; Faizatun Nazilah; Diska Fratiwi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Data showed the existence of problems found in 4th grade during Indonesian Language learning in reading comprehension material. Reading comprehension aims to obtain information from the text. Problems are found in two important aspects of learning; teacher performance and student activities. The discovery of the problem is because the teacher uses a learning method that makes students less enthusiastic when delivering learning material. For this reason, classroom action research was conducted using a spiral model from Kemmis and Taggart. The corrective action taken is to apply the mind mapping learning model. Mind mapping is designed to help students to easily remember and understand the information that contained in the text. Preliminary data explained that 9 students completed learning or 33.33% of 27 students. The action is carried out in two cycles. It is because new targets are reached in the second cycle. From the results, we can concluded that mind mapping is able to improve student learning outcomes in reading material understanding in Indonesian language learning